Provinciální synody hnězdenské církevní provincie do začátku 16. století - Krafl, Pavel (Prawo Kanoniczne, 2000)
It was relatively early that the archbishops of Gniezno began to convoke provincial synods - the oldest dated assembly which is marked in the sources as a provincial synod took place as early as in 1210. But even before this synod another provincial synod took place in 1206 (?). In the beginning, i. e. in the thirteenth century, it is important to distinguish clearly between bishops' conventions, or colloquia, and provincial synods. The first statutes backed up with evidence are the statutes issued by Archbishop Henryk Kietlicz around 1217 in Kamień. Another important archbishop was Pełka (Fulko, 1232 - 1258). Two statutes issued by this metropolitan are still preserved. An important role in the system of provincial legislation was played by legates' synods and the legates' statutes which were proclaimed at them. A number of provincial synods was summoned by the archbishop of Gniezno Jakub Świnka (1285, 1287,1290,1298, 1306, 1309). Several not dated fragments of statutes originate from his time. In the fourteenth century the situation changes - the only two provincial synods that we know of are the synods of Janisław (1326) and Jarosław Bogoria Skotnicki (1357). „Synodyk“, the first attempt at codification of the legislation of Gniezno church province, comes from Skotnicki's synod. We cannot agree with referring to the assembly at Krakow from 1356 as to a provincial synod. Similarly, the „convencio generalis“ in Łęczyca in 1402 could not have been a provincial synod. Thus the first reliably proved provincial synod of the fifteenth century is the synod of Mikołaj.